Characteristics and Scoring Model of COVID-19 Severity Predictor in Obstetric and Gynecology Doctors in Indonesia - Sutrisno Sutrisno; Wening Hapsari (Fertility & Reproduction, 2022)
Background: Obstetrician and gynecologist are one of the contributors in patient care who are susceptible to contracting coronavirus-19 infection. Emergency measures for maternal field are high, while gold standard examination for COVID-19 takes long time with false negative rate. The case fatality rate of COVID-19 among health workers in Indonesia is reported to be high. We want to know epidemiological, clinical, and occupational characteristics of various degrees of COVID-19 severity and create scoring model to predict COVID-19 severity in ob/gyn doctors in Indonesia. Method: This is a descriptive analytic study using a cross-sectional approach. Consecutive sampling was taken from ob/gyn doctors infected with COVID-19 and analyses used were Chi-Square and Mann-Whitney U tests. A scoring model is created and using receiver operating characteristic (ROC) curves, to determine the predictive ability of the scoring model and the cutoff value to COVID-19 severity, then tested for sensitivity and specificity. Result: The mean age of the respondents was 38.2 ± 9.8 and 48.7% were male. Sixty-one percent respondents experienced mild symptoms, infected while on duty (46.1%), and 59% had nuclear family member infected with COVID-19. Age group ([Formula: see text] = 0.000), number of infection ([Formula: see text] = 0.000), vaccination status ([Formula: see text] = 0.010), comorbidities ([Formula: see text] = 0.023), and working hours ([Formula: see text] = 0.002) were significantly different on the COVID-19 severity. Area-under-curve of scoring model was 75.2% and 93.4%. The cutoff value was 10.5 points for between asymptomatic and mild degree (sensitivity 54.2% and specificity 77.8%) and 12.5 points between mild and moderate degree (sensitivity 83.3% and specificity 95.8%) respectively. Conclusion: The developed scoring model can facilitate prediction of COVID-19 severity in ob/gyn doctors, with asymptomatic (score of < 10.5 points), mild degree (score of 10.5–12.5 points), and moderate degree (score of > 12.5 points).